Aunt Dimity and the Summer King [large type] - Atherton, Nancy (Atherton, Nancy. Aunt Dimity series., 2015)
Overseeing her baby, a family wedding and her own approaching 40th birthday celebration amid rumors that a developer has unwanted plans for Finch village, Lori bonds with a warmhearted inventor only to discover his true intentions.